264 THE DIAGNOSTIC UTILITY OF ATTENUATION CORRECTION OF SPECT MYOCARDIAL PERFUSION IMAGING FOR THE DETECTION OF LAD DISEASE. (1st January 2006) - Bhatti, T. K.; DePasquale, E. E.; Nody, A. C.; Kesanakurthy, S.; Panagopoulos, G.; Coplan, N. C.
Abstract : Objectives: Attenuation correction (AC) in combination with SPECT imaging has been shown to decrease false-positive results and thereby increase the specificity of myocardial perfusion imaging. Some patients have been shown to have new perfusion defects on AC that are not apparent with conventional reconstruction (CR). The purpose of this study is to determine the diagnostic significance of perfusion defects in the LAD territory noted only on attenuation-corrected stress images. Methods: 150 patients (105 males, 45 females) who had undergone a 2-day rest Tl-201/stress Tc-99m tetrafosmin gated SPECT protocol and subsequent coronary angiography within 3 months were studied. All images were acquired using VantagePro/Ex SPECT II (ADAC). The studies were processed with CR and with AC and were interpreted blindly by two expert readers. Scan findings were correlated with angiographic disease by quantitative coronary angiography, and the CR and AC studies were compared for their accuracy in detecting angiographic evidence of LAD stenosis (> 50%). Statistical comparisons were performed using a comparison of two proportions and the McNemar's test. Results: The patients had a mean age of 61 years (6 11.7 years); 15% had diabetes mellitus, 35% had hypertension, 40% had hyperlipidemia, and 10% were active smokers. The sensitivity for detecting coronary artery disease (CAD) in the LAD territory increased from 64% using CR images to 92% with AC (p < .001), while the specificity did not show a significant increase from 62% to 74% (p = .18). There was a trend for a significant increase in the positive predictive value of CR from 70% to 84% with AC (p = .063). The negative predictive value of CR was 54% and increased to 87% with AC (p < .001). Overall, using McNemar's test, there was a significant change in test results when comparing CR to AC (p = .017). Conclusions: New perfusion defects identified using attenuation-corrected images are highly accurate in identifying significant CAD in the distribution of the LAD territory. The use of AC resulted in the improved detection of CAD over uncorrected SPECT studies.